PENINGKATAN PENERIMAAN NEGARA BUKAN PAJAK MELALUI PENGELOLAAN BARANG MILIK NEGARA KEMENTERIAN PERTAHANAN - Muhtar Rifai; Ansar Tutu; Zainal Abidin Sahabuddin; Anton Imam Santosa (DAS Institute, 2022)
(BMN) and is oriented towards public services and public welfare. Government Regulation Number 28 of 2020 concerning Amendments to Government Regulation Number 27 concerning Management of State/Regional Property becomes the basis for managing state assets through the use of State Property to increase state revenue in the form of Non-Tax State Revenue (PNBP). State property utilization must be carried out professionally, effectively, and accountably by considering aspects of physical feasibility, legal feasibility, financial feasibility, and asset productivity feasibility. This research was conducted qualitatively with primary data sources derived from interviews and secondary data sources derived from documents or other valid information. The results of the study show that: (1) Management of State Property of the Ministry of Defense of the Republic of Indonesia is carried out to increase PNBP that has not been optimally achieved, (2) The idle BMN has not been efficient with the highest and best use and the management of PNBP on the use of BMN has not been fully following the Budget mechanism. State Revenue and Expenditure, (3) The need for optimization of supervision and control on the management of State Property, Ministry of Defense.